Advances in sustainable additive manufacturing: a systematic review for construction industry to mitigate greenhouse gas emissions - Oladunni, Oluwole Joseph; Lee, Carman K. M.; Ibrahim, Idowu David; Olanrewaju, Oludolapo Akanni (Frontiers in Built Environment, 2025)
Background and ObjectiveAdditive Manufacturing (AM), driven by digital 3D design data, is a transformative technology that holds significant potential to revolutionize the construction industry. Its untapped capacity to optimize material utilization, enhance design flexibility, and substantially reduce greenhouse gas (GHG) emissions emplaces it as key enabler to sustainable construction. Although being adopted in biomedical, aerospace, and automotive industries, AM remains underexplored in construction. This study systematically evaluates the role of AM in advancing sustainable construction, particularly its impact on reducing GHG emissions.Materials and methodsSystematic research was conducted using resourceful methodologies. These are to include PRISMA meta-analysis, Cochrane Collaboration, EPPI-Reviewer 4, VOSviewer, and Databases with Search Engines. The tools were employed to synthesize, organize, and to deduce relevant materials and literature, facilitating comparative analyses of AM and traditional (conventional) subtractive manufacturing (TSM). The systematic review essentially concentrates on metrics such as design process efficiency, cost-effectiveness, production rates, and material sustainability. Furthermore, on diverse AM techniques, and materials, to include concrete, composites, and polymers, being evaluated for their potential to mitigate carbon emissions.ResultsQuantitatively, the results connote that AM can better enhance energy efficiency by up to 60%, reduce material waste by 90%, and cushioned to lower GHG emissions by 80%, while achieving labour and cost savings of 50%–60%, and sustainability by 75% in specific design standards. Furthermore, AM enables the production of complex geometrical designs that are unfeasible with conventional methods, improving both structural and mechanical performance, and sustainability.ConclusionThis study expounds the environmental, social and economic benefits of AM, providing highly valuable insights to further incorporate AM to contemporary construction as viable alternative solutions, and sustainable supplements to TSM. Additive manufacturing innovations are deduced to be well positioned as significant strategic driver for eco-friendly built environment, supporting global efforts toward carbon neutrality and sustainable urban developments.